Multiple myeloma and physical activity: a scoping review. Issue 11 (27th November 2015) - Smith, Lee; McCourt, Orla; Henrich, Malgorzata; Paton, Bruce; Yong, Kwee; Wardle, Jane; Fisher, Abigail
Abstract : Objectives: Multiple myeloma is the second most common haematological cancer. A growing body of literature is emerging that investigates the role physical activity plays in all stages of multiple myeloma (prevention and survivorship) and to date no attempt has been made to collate and understand this literature. Therefore, this scoping review aims to (1) outline what is already known about physical activity in all stages of multiple myeloma (2) map the literature on physical activity and multiple myeloma and (3) identify future directions for research. Design: Scoping Review. Data Sources: Searches were carried out in May 2015. Searchers were conducted in PubMed, Web of Science, SPORTdiscus and MEDLINE. Eligibility criteria for selecting studies: To be included studies had to report original data, investigate physical activity per se or physical activity correlates and multiple myeloma or smouldering multiple myeloma. Results: A total of 19 papers received full screening, 5 of these papers were excluded. This review identified three journal articles relating to the role of physical activity in the prevention of multiple myeloma, nine papers were identified in the treatment of multiple myeloma and two on smouldering multiple myeloma. Conclusions: The search identified that the literature surrounding multiple myeloma and physical activity is very limited. We encourage those designing new cohort studies to allow for future assessment of associations between physical activity and onset of multiple myeloma and smouldering multiple myeloma, as well as the potential role that physical activity plays in the progression from smouldering multiple myeloma to multiple myeloma. Second, we encourage the design and investigation of gender and treatment-specific physical activity interventions in patients with multiple myeloma. Finally, we highlight the need for more randomised controlled trials to evaluate the impact of different types, frequencies and intensities of physical activity on various health parameters in multiple myeloma survivors.